ALANA KUMBIER, Ephemeral Material: Queering the Archives - Sheffield, Rebecka (Archivaria, 2016)
Ephemeral Material: Queering the Archives. ALANA KUMBIER. Sacramento, CA: Litwin Books, 2014. 266 pp. ISBN 978-1-936117-51-2